PENGARUH KEPEMIMPINAN DAN STRATEGI KERJA TERHADAP HASIL KERJA DI PT PULAHAN SERUWAI - Putra, Azlansyah (CV. Lafadz Jaya, 2024)
Leadership and Work Strategy are important aspects for achieving results. There are many results from leadership and work strategy if everything is carried out properly and will produce the work performance that is the goal. The purpose of this writing is to analyze and determine the influence of work strategy and training on work results at PT Pulahan Seruwai, Air Batu District, Asahan Regency. The results of SPPSS 16 analysis of Leadership questionnaire data, and work strategies on Work Performance at PT Pulahan Seruwai, Air Batu District, Asahan District, namely (1) partially the Leadership variable influences the work performance of workers at PT Pulahan Seruwai, Air Batu District, Asahan District, (2) partially, the work strategy variable influences the work performance of workers at PT Pulahan Seruwai, Air Batu District, Asahan Regency, (3) simultaneously there is a positive and significant influence between the Leadership and work Strategy variables on the work performance of workers at PT Pulahan Seruwai, Air Batu District, Asahan District.